2000
DOI: 10.1038/modpathol.3880220
|View full text |Cite
|
Sign up to set email alerts
|

Immunophenotype of High-Grade Prostatic Adenocarcinoma and Urothelial Carcinoma

Abstract: Morphologic features alone can usually be used to distinguish prostatic adenocarcinoma and urothelial carcinoma of the urinary bladder. Poorly differentiated tumors, however, can occasionally have features of both neoplasms, making determination of site of origin difficult. No study has provided a panel of antibodies to assist in the distinction of these two tumors. For this study, 73 examples of moderately and poorly differentiated prostatic adenocarcinoma and 46 examples of high-grade urothelial carcinoma we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
87
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(95 citation statements)
references
References 35 publications
7
87
1
Order By: Relevance
“…7 As we have shown, an immunohistochemical panel that includes CK7, CK20, and 34bE12 can be useful in establishing the correct diagnosis. Positive staining for CK7 and 34bE12, with or without positive immunoreactivity for CK20, represents the immunophenotype expected for carcinomas of urothelial origin 8 and supports the diagnosis of urothelial-type adenocarcinoma. Tamboli et al 9 have shown that the addition of villin to such a panel is helpful in distinguishing between colonic adenocarcinoma metastatic to the urinary tract (villin positive) and primary urothelial carcinoma showing glandular differentiation (villin negative).…”
Section: Discussionmentioning
confidence: 52%
“…7 As we have shown, an immunohistochemical panel that includes CK7, CK20, and 34bE12 can be useful in establishing the correct diagnosis. Positive staining for CK7 and 34bE12, with or without positive immunoreactivity for CK20, represents the immunophenotype expected for carcinomas of urothelial origin 8 and supports the diagnosis of urothelial-type adenocarcinoma. Tamboli et al 9 have shown that the addition of villin to such a panel is helpful in distinguishing between colonic adenocarcinoma metastatic to the urinary tract (villin positive) and primary urothelial carcinoma showing glandular differentiation (villin negative).…”
Section: Discussionmentioning
confidence: 52%
“…It is recognized that p53 gene alteration is one of the important pathways leading to high-grade urothelial carcinoma with p53 immunohistochemical expression seen in 27.2-66% of urothelial carcinomas. 33,34 Based on our study, osteoclast-like giant-cell carcinomas of the urothelial tract should be considered as variants of urothelial carcinoma. Evidence to support this conclusion are: (1) the presence of keratin positivity in the majority of cases; (2) association with conventional urothelial carcinoma; and (3) matched p53 positivity in both the mononuclear cells and the accompanying urothelial neoplasm.…”
Section: Osteoclast-like Giant-cell Neoplasms D Baydar Et Almentioning
confidence: 87%
“…3 It has been demonstrated that even some cases of primary prostate cancer were negative for PSA but could be detected by prostate-specific acid phosphatase (PSAP) and thus might be a good additional marker. 7,8 In contrast to PSA, prostate-specific membrane antigen (PSMA) and prostein (also known as p501s or SLC45A3) were recently described to be highly specific for prostatic tissue. 9,10 Since TMPRSS2-ERG rearrangements, leading to an ETSrelated gene (ERG) overexpression, 11 are amongst the most common and disease-specific genetic alterations in locally defined prostate cancer, [12][13][14] ERG might be of diagnostic potential.…”
mentioning
confidence: 99%